Arrhythmic mitral valve prolapse in 2023: Evidence-based update - Kubala, Maciej; Essayagh, Benjamin; Michelena, Hector I.; Enriquez-Sarano, Maurice; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2023)
Patients with mitral valve prolapse (MVP) may develop ventricular arrhythmias, ranging from premature ventricular contractions through more complex non-sustained ventricular tachycardia to sustained life-threatening ventricular arrhythmias. The prevalence of MVP in autopsy series of young adults who died suddenly has been estimated to be between 4% and 7%. Thus, “arrhythmic MVP” has been reported as an underappreciated cause of sudden cardiac death, leading to a renewed interest in the study of this association. The term “arrhythmic MVP” refers to a small subset of patients who have, in the absence of any other arrhythmic substrate, MVP, with or without mitral annular disjunction, and frequent or complex ventricular arrhythmias. Our understanding of their coexistence in terms of contemporary management and prognosis is still incomplete. While literature regarding the arrhythmic MVP may be contrasting despite recent consensus document, the present review summarizes the relevant evidence concerning the diagnostic approach, prognostic implications, and targeted therapies for MVP-related ventricular arrhythmias. We also summarize recent data supporting left ventricular remodeling, which complicates the coexistence of MVP with ventricular arrhythmias. As the evidence for a putative link between MVP-associated ventricular arrhythmias and sudden cardiac death is scarce and based on scant and retrospective data, risk prediction remains a challenge. Thus, we aimed at listing potential risk factors from available seminal reports for further use in a more reliable prediction model that requires additional prospective data. Finally, we summarize evidence and guidelines on targeted therapies of ventricular arrhythmias in the setting of MVP, including implantable cardioverter defibrillators and catheter ablation. Our review highlights current knowledge gaps and provides an action plan for structured research on the pathophysiological genesis, diagnosis, prognostic impact, and optimal management of patients with arrhythmic MVP.